Azobenzene Photoswitches in Proteolysis Targeting Chimeras: Photochemical Control Strategies and Therapeutic Benefits. Issue 23 (14th June 2022) - Negi, Arvind; Kieffer, Charline; Voisin‐Chiret, Anne Sophie
Abstract: The photoswitchable‐PROTACs have photoswitches that work as an actual ON/OFF switch for any particular bioactivity. In reported studies, the ON/OFF activity correlates with the photostationary state and quantum yield of a specific isomer under a definite wavelength of light, providing a spatiotemporal control over protein degradation (an example of photochemistry‐based precision medicine). The studies reported the role of azobenzenes as photoswitches ( ortho ‐tetramethoxybenzenes, ortho‐tetraflurobenzenes as push‐pull and push‐push) to develop light‐controlled PROTACs. This paper discussed the photophysical properties of photoswitchable‐PROTACs (such as photoisomerization, quantum yield, and thermal relaxation states) and correlated their photochemical‐based structural bioactivity relationships. The proteins studied under photoswitchable‐PROTACs are kinase proteins: BCR‐ABL fusion protein, ABL; Bromodomain proteins: BRD2, 3, 4; Immunophilins: FKBP12. Abstract : Azobenzene‐based photoswitches provide a photochemical handle to PROTACs over their degradation activity towards a specific protein of interest. This paper summaries strategy, structural activity relationships, and photophysical properties of azobenzene photoswitches in those PROTACs. This date, the successful implication of azobenzene photoswitch‐based photochemical degradation is limited to some proteins: kinase (BCR‐ABL), bromodomain (BRD2‐4), and FKBP12.